Inflammatory markers and calcification of coronary arteries, aorta and cardiac valves: Findings from the atherosclerosis risk in communities study - Vennela Avula; Yejin Mok; Kentaro Ejiri; Jeremy Van't Hof; Seamus P. Whelton; Ron C. Hoogeveen; Christie M. Ballantyne; Matthew J Budoff; Michael J Blaha; Kunihiro Matsushita (American Journal of Preventive Cardiology)
Background: Inflammation plays an important role in the pathophysiology of atherosclerosis. However, inflammatory biomarkers have only been weakly associated with coronary artery calcium (CAC), a representative measure of subclinical atherosclerosis. Moreover, few studies explored extra-coronary calcium (ECC) in this context. Aim: To characterize the association of two inflammatory markers, high-sensitivity C-reactive protein (hs-CRP) and galectin-3, at middle age with CAC and ECC at older age in a community-based cohort. Methods: Cardiac CT was performed among 1,930 Atherosclerosis Risk in Communities (ARIC) study participants (age 73–95) without coronary heart disease at visit 7 (2018–19). We examined the associations of hs-CRP and galectin-3 measured (age 53–74 years) at visit 4 (1996–98) by quartile with the presence of CAC and ECC (Agatston score >0 vs. 0) using multivariable logistic regression. Results: Higher hs-CRP was associated with the presence of calcifications in the ascending aorta, aortic valve ring, mitral valve, left main, left anterior descending, left circumflex, right coronary artery, and total CAC in the demographic (race, sex, age, and ARIC center) adjusted model. These associations were mostly attenuated after adjusting for potential confounders, but the associations with ascending aorta and right coronary artery calcifications remained significant (adjusted odds ratio [aOR] 1.45 [95 % CI 1.02–2.07]) and 1.55 [1.12–2.16]) for the highest vs. lowest quartiles, respectively. Galectin-3 was also independently associated with right coronary artery calcification after adjusting for potential confounders of interest (aOR 1.48 [1.02 – 2.01]) for the highest vs. lowest quartiles. These associations were generally consistent in demographic subgroups. Conclusions: Both hs-CRP and galectin-3 were associated with calcification of some but not all vascular beds tested, suggesting potentially unique atherosclerotic pathophysiology across different vascular beds. Robust associations of inflammatory markers with right coronary artery calcification deserve further investigation.